Pengaruh Keputusan Investasi, Keputusan Pendanaan, Struktur Modal terhadap Nilai Perusahaan dengan Kinerja Keuangan Sebagai Variabel Intervening pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia - Devira Larasati; Hwihanus Hwihanus (Jurnal Mutiara Ilmu Akuntansi, 2024)
With financial performance as an intervening variable, this study tries to test and assess the relationship between capital structure, funding decisions, and investment decisions on firm value in food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange. All food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange between 2020 and 2022 are the population in this study. Purposive sampling is the method used to obtain samples in this study. Ten companies that fit the research requirements were found using purposive sampling technique. Partial Least Square was used in data analysis and hypothesis testing in this study. There are 7 hypotheses in this study. The results prove that there are 6 hypotheses that have a negative and insignificant effect. While 1 hypothesis has a positive and insignificant effect.